Impact of different structural types of amylopectin on retrogradation. (July 2018) - Vamadevan, Varatharajan; Bertoft, Eric
Abstract: Retrogradation is the re-association and recrystallization process of glucan chains in gelatinized starch. The objective of the study was to investigate the effect of amylopectin structure on re-association of glucan chains during retrogradation. Amylopectin retrogradation of 17 starches from four different structural types was examined by differential scanning calorimetry (DSC). Gelatinized starches were stored for 10 days at 4 °C and then scanned from 10–120 °C at 10 °C/min. The structural type of amylopectin influenced the transition temperatures (Tm and Tc ), melting temperature range (Tc –To ) and enthalpy change of transition (ΔH). Correlation analysis between different chain length categories and the melting parameters of recrystallized amylopectin revealed a strong correlation of the external chain length (ECL) with Tm (r = 0.90, p < 0.01), Tc (r = 0.95, p < 0.01), Tc –To (r = 0.89 p < 0.01), and ΔH (r = 0.89, p < 0.01) showing the importance of the external chains of amylopectin in the recrystallization process. Chains with very short external length (ECL 6–8) showed negative relationship with retrogradation behavior. However, also the inter-block chain length (IB-CL; distance between tightly branched units) showed positive correlation with transition temperatures (Tc : r = 0.96, p < 0.01, Tc –To : r = 0.97, p < 0.01), and ΔH (r = 0.91, p < 0.01) suggesting that longer internal chain segments also play an important role, possibly by contributing to a flexible amylopectin structure. The retrogradation behavior of amylopectin types can be systematically interpreted with the backbone model of amylopectin. Graphical abstract: Image 1 Highlights: Retrogradation properties are determined by external and internal amylopectin structure. External and inter-block chain lengths correlate with thermal properties of retrograded starch. Very short external chains prevent retrogradation. Retrogradation is explained through the building block backbone model of amylopectin.